The Effect of Realistic Mathematics Approach on Mathematical Problem Solving Ability of Elementary School Students - Hasrinah Hafid; Agustan Syamsuddin; Sulfasyah Sulfasyah (Institut Agama Islam Negeri Palopo, 2022)
This study aims to examine the impact of a realistic mathematics approach on the mathematical problem-solving abilities of elementary school students. It employed a quantitative research method with a non-equivalent control group design. The study's participants were fifth-grade students from various schools in Tanete Rilau District, Barru Regency. The sample was selected using simple random sampling. Data collection involved a mathematics problem-solving ability test. The analysis included descriptive and inferential techniques. Descriptive analysis revealed that students in the experimental class, taught using a realistic mathematics approach, demonstrated significantly better problem-solving skills compared to those in the control class. The average posttest score in the experimental class was 61.85, whereas it was 46.40 in the control class. Inferential analysis, including independent sample t-test and Manova test, indicated that learning with a realistic mathematics approach had a significant effect, as evidenced by a sig value of 0.000, which is less than 0.05.